Resistance of Primary Photosynthesis to Photoinhibition in Antarctic Lichen Xanthoria elegans : Photoprotective Mechanisms Activated during a Short Period of High Light Stress - Hajek, Josef; Bartak, Milos; Mishra, Kumud Bandhu; Puhovkin, Anton; Giordano, Davide; Bednarikova, Michaela; Casanova-Katny, Angelica; Vaczi, Peter; Halici, Mehmet Goekhan (Plants, 2023)
The Antarctic lichen, Xanthoria elegans, in its hydrated state has several physiological mechanisms to cope with high light effects on the photosynthetic processes of its photobionts. We aim to investigate the changes in primary photochemical processes of photosystem II in response to a short-term photoinhibitory treatment. Several chlorophyll a fluorescence techniques: (1) slow Kautsky kinetics supplemented with quenching mechanism analysis; (2) light response curves of photosynthetic electron transport (ETR); and (3) response curves of non-photochemical quenching (NPQ) were used in order to evaluate the phenomenon of photoinhibition of photosynthesis and its consequent recovery. Our findings suggest that X. elegans copes well with short-term high light (HL) stress due to effective photoprotective mechanisms that are activated during the photoinhibitory treatment. The investigations of quenching mechanisms revealed that photoinhibitory quenching (qIt) was a major non-photochemical quenching in HL-treated X. elegans; qIt relaxed rapidly and returned to pre-photoinhibition levels after a 120 min recovery. We conclude that the Antarctic lichen species X. elegans exhibits a high degree of photoinhibition resistance and effective non-photochemical quenching mechanisms. This photoprotective mechanism may help it survive even repeated periods of high light during the early austral summer season, when lichens are moist and physiologically active.